Active iron species driven hydroxyl radicals formation in oxygenation of different paddy soils: Implications to polycyclic aromatic hydrocarbons degradation. (15th September 2021) - Chen, Ning; Huang, Danyu; Liu, Guangxia; Chu, Longgang; Fang, Guodong; Zhu, Changyin; Zhou, Dongmei; Gao, Juan
Highlights: The OH production largely differed in oxygenation of different paddy slurries. The OH production was highly hinged on the content of active Fe species. Active Fe species are exchangeable, surface-bound and low-crystalline Fe phases. The produced OH can efficiently degrade PAHs in paddy slurries. Abstract: The frequently occurring redox fluctuations in paddy soil are critical to the cycling of redox-sensitive elements (e.g., iron (Fe) and carbon) due to the driving of microbial processes. However, the associated abiotic process, such as hydroxyl radical ( OH) formation, was rarely investigated. Hence, we examined the under-appreciated role of OH formation in driving polycyclic aromatic hydrocarbons (PAHs) degradation upon oxygenation of anoxic paddy slurries. Results showed that OH production largely differed in different paddy slurries, in the range of 271.5-581.2 μ mol kg −1 soil after 12 h reaction. The OH production was highly hinged on the contents of active Fe species, i.e., exchangeable, surface-bound Fe and Fe in low-crystalline phases rather than Fe in high-crystalline minerals or silicates. Besides, OH production significantly decreased with increasing soil depth due to the declined active Fe species and abundance of functional microbes. Oxygenation also induced the transformation of these active Fe species into the low- and high-crystalline phases, which might affect the following redox process. The produced OH can efficiently degrade PAHs with degradation extents depending on their physiochemical properties. Our findings highlight the key roles of active Fe species in driving OH formation and organic contaminants degradation during redox fluctuations of paddy soils. Graphical abstract: Image, graphical abstract